The occupational therapist as a political being/O terapeuta ocupacional como um ser político - Pollard, Nick; Sakellariou, Dikaios (Cadernos Brasileiros de Terapia Ocupacional, 2014)
In this article we argue for the development of an understanding of human occupation as being inherently political. Occupational therapy is broadly about the experience of ‘doing’ as the basis of social participation. This requires access to the means of participation: space, facilities and resources for different forms of human action, and occupational therapists need to develop an understanding of how access to these means is regulated. In this article we develop an argument for the development of a political occupational therapy. We do this by outlining the role of occupational therapists as activists as well as reflectors drawing on comparisons with cultural practice in community publishing; by discussing the development of a language that will enable the recognition and exploration of power differentials, and by delineating the importance of experiential knowledge.